Back Cover: Ligand Dilution Analysis Facilitates Aptamer Binding Characterization at the Single‐Molecule Level (Angew. Chem. Int. Ed. 10/2023) - Du, Yulin; Lyu, Yifan; Li, Shiquan; Ding, Ding; Chen, Jianghuai; Yang, Cai; Sun, Yang; Qu, Fengli; Xiao, Zeyu; Jiang, Jianhui; Tan, Weihong (Angewandte Chemie International Edition, 2023)
A membrane‐receptor‐analysis method termed ligand dilution analysis, which combines the concepts of single‐molecule localization and random sampling, is reported by Yifan Lyu, Jianhui Jiang, Weihong Tan et al. in their Research Article (e202215387). Aptamer binding characterization, including receptor density calculation, single‐molecule colocalization, binding site determination, motion and fluctuation analysis, was performed with minimal probe and instrument requirements.